Approximation of linear functionals using an hp-adaptive discontinuous Galerkin finite element method - Harriman, K; Gavaghan, D; Suli, E (Unspecified, 2004)
We consider the problem of computing a linear functional of the solution of an elliptic partial differential equation to within a given tolerance. We drive an a posteriori error bound for the linear functional and use this as the basis of an hp-adaptive discontinuous Galerkin finite element algorithm to deliver the functional to within a prescribed error tolerance.